Interest Groups, NGOs or Civil Society Organisations? The Framing of Non-State Actors in the EU - Jonas J. Schoenefeld (VOLUNTAS: International Journal of Voluntary and Nonprofit Organizations, 2020)
Scholars have used varying terminology for describing non-state entities seeking to influence public policy or work with the EU's institutions. This paper argues that the use of this terminology is not and should not be random, as different `frames' come with different normative visions about the role(s) of these entities in EU democracy. A novel bibliometric analysis of 780 academic publications between 1992 and 2020 reveals that three frames stand out: The interest group frame, the NGO frame, as well as the civil society organisation frame; a number of publications also use multiple frames. This article reveals the specific democratic visions contained in these frames, including a pluralist view for interest groups; a governance view for NGOs as `third sector' organisations, and participatory and deliberative democracy contributions for civil society organisations. The use of these frames has dynamically changed over time, with `interest groups' on the rise. The results demonstrate the shifting focus of studies on non-state actors in the EU and consolidation within the sub-field; the original visions of European policy-makers emerging from the 2001 White Paper on governance may only partially come true.
Keywords: 300; Interest group; NGO; Civil society organisation; Lobbying; Framing; EU